Evaluation the efficacy of narrow band ultraviolet B phototherapy in childhood vitiligo - khadam, jamal (Latakia University Journal -Medical Sciences Series, 2023)
Vitiligo is an idiopathic acquired dermatosis characterized by depigmented macules or patches, affects 0.5-2% of the world-wide papulation, and half of the patients suffering onset of the depigmentation prior of the age of 20 years. Narrow band ultraviolet B (NB-UVB) treatment is commonly used of psoriasis and atopic dermatitis, and is less often used for vitiligo in children. The aim of this study was to evaluate the efficacy and short-term safety of NB-UVB phototherapy in children diagnosed with vitiligo. Materials and methods: 24 children patients with diagnosis of vitiligo (10 males and 14 females), aged 4-16 years, were treated twice weekly with NB-UVB radiation therapy for a maximum period of one year, and were followed-up for six months for stability of repigmentation. Clinical response was assessed according to repigmentation of the lisions: good response when there was more than 75% repigmentation, moderate when there was 25-75% repigmentation, poor response when repigmentation was 1-24%, and unresponsive when there no repigmentation. Results: analysis of this study showed that 11(45.8%) of cases had more than 75% to complete repigmentation, 6(25%) achived 25-75% moderate repigmentation, 5(20.8%) had 1-24% mild repigmentation, only 2 (8.4%) of cases did not response to NB-UVB and also 2 cases developed depigmentation of repigmentation sites during 6 months follow-up. Adverse effects were transient and minimal. Conclusion: NB-UVB therapy is effective and safe tool in the management of childhood vitiligo, with good stability of repigmentation.